KONTRIBUSI HUTAN RAKYAT KEMENYAN (Styrax spp.) TERHADAP PENDAPATAN RUMAH TANGGA PETANI (Studi Kasus : Desa SimarigungKecamatan DoloksanggulKabupaten Humbang HasundutanSumatera Utara) - Binton Harianto purba; Evi Sri Budiani; M Mardhiansyah M Mardhiansyah (Fakultas Pertanian, Universitas Riau, 2017)
The community forests management of Styrax spp.becomes a culture and the source of life and social prestige of a family which is measured by the size of the Styraxspp. garden owned and has even become part of the life of the Sytraxspp. farmerin HumbangHasundutan, especially Simarigung Village. As time goes by, many Styraxspp. farmers are turning into horticultural farmers to sufficethe needs of farmers. The purpose of this research is to know the pattern of cultivation of Sytraxspp. plants, to know the contribution of Sytrax spp. plants to household income, and the factors causing the low income of Styrax spp. farmers in Simarigung Village. Sampling method were taken by simple random sampling. The study population was all the head of the family in the Village Simarigung as many as 225 families. The research sample is 20% 25 families of 125 families who manage Styrax spp. The results showed that the major contribution to the community forests of Styraxspp. about household income in the Village Simarigung around Rp. 10.810.000,00- Rp. 22.220.000,00/year and overall was 47.64% or Rp. 457.390.000.00/year. In research show that the management of Sytrax spp. is still traditional and monoculture.The low income of Styraxspp.due to old age and younger Styraxspp. that cannot be notched and lack of maintenance can reduce the quantity and quality of Styraxspp. resin production.